Model of Islam Nusantara da'wah based on multiculturalism - Muhyiddin, Ahmad Shofi (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2023)
Purpose - This study aims to develop a model of Islamic da'wah based on religious and cultural multiculturalism in Indonesia as a response to religious violence.Method - This research was conducted through a literature review (library research) with a philosophical hermeneutic approach in which data related to da'wah scholarship, the term Islam Nusantara, and multiculturalism were analyzed using descriptive-holistic-heuristic elements.Result - The results of the study show that: 1). Islam Nusantara da'wah necessitates the presence of Islam, which is constantly in dialectics with the culture of the people of the Archipelago. In this dialectical process of Islam and culture, it is not uncommon for